A quantitative real-time assessment of Buerger exercise on dorsal foot peripheral skin circulation in patients with diabetes foot. Issue 46 (November 2016) - Chang, Chang-Cheng; Chen, Men-Yen; Shen, Jen-Hsiang; Lin, Yen Bin; Hsu, Wen-Wei; Lin, Bor-Shyh
Abstract : Abstract: Buerger exercise can improve the peripheral circulation of lower extremities. However, the evidence and a quantitative assessment of skin perfusion immediately after this exercise in patients with diabetes feet are still rare. We recruited 30 patients with unilateral or bilateral diabetic ulcerated feet in Chang Gung Memorial Hospital, Chia-Yi Branch, from October 2012 to December 2013. Real-time dorsal foot skin perfusion pressures (SPPs) before and after Buerger exercise were measured and analyzed. In addition, the severity of ischemia and the presence of ulcers before exercise were also stratified. A total of 30 patients with a mean age of 63.4 ± 13.7 years old were enrolled in this study. Their mean duration of diabetes was 13.6 ± 8.2 years. Among them, 26 patients had unilateral and 4 patients had bilateral diabetes foot ulcers. Of the 34 wounded feet, 23 (68%) and 9 (27%) feet were classified as Wagner class II and III, respectively. The real-time SPP measurement indicated that Buerger exercise significantly increased the level of SPP by more than 10 mm Hg (n = 46, 58.3 vs 70.0 mm Hg, P < 0.001). In terms of pre-exercise dorsal foot circulation condition, the results showed that Buerger exercise increased the level of SPP in severe ischemia (n = 5, 22.1 vs 37.3 mm Hg, P = 0.043), moderate ischemia (n = 14, 42.2 vs 64.4 mm Hg, P = 0.001), and borderline–normal (n = 7, 52.9 vs 65.4 mm Hg, P = 0.028) groups, respectively. However, the 20 feet with SPP levels more than 60 mm Hg were not improved significantly after exercise (n = 20, 58.3 vs 71.5 mm Hg, P = 0.239). As to the presence of ulcers, Buerger exercise increased the level of SPP in either unwounded feet (n = 12, 58.5 vs 66.0 mm Hg, P = 0.012) or wounded feet (n = 34, 58.3 vs 71.5 mm Hg, P < 0.001). The majority of the ulcers was either completely healed (9/34 = 27%) or still improving (14/34 = 41%). This study quantitatively demonstrates the evidence of dorsal foot peripheral circulation improvement after Buerger exercise in patients with diabetes.